A contribution of star-forming clumps and accreting satellites to the mass assembly of z ∼ 2 galaxies. Issue 2 (5th August 2019) - Zanella, A; Le Floc'h, E; Harrison, C M; Daddi, E; Bernhard, E; Gobat, R; Strazzullo, V; Valentino, F; Cibinel, A; Sánchez Almeida, J; Kohandel, M; Fensch, J; et al.
ABSTRACT: We investigate the contribution of clumps and satellites to the galaxy mass assembly. We analysed spatially resolved HubbleSpace Telescope observations (imaging and slitless spectroscopy) of 53 star-forming galaxies at z ∼ 1–3. We created continuum and emission line maps and pinpointed residual 'blobs' detected after subtracting the galaxy disc. Those were separated into compact (unresolved) and extended (resolved) components. Extended components have sizes ∼2 kpc and comparable stellar mass and age as the galaxy discs, whereas the compact components are 1.5 dex less massive and 0.4 dex younger than the discs. Furthermore, the extended blobs are typically found at larger distances from the galaxy barycentre than the compact ones. Prompted by these observations and by the comparison with simulations, we suggest that compact blobs are in situ formed clumps, whereas the extended ones are accreting satellites. Clumps and satellites enclose, respectively, ∼20 per cent and ≲80 per cent of the galaxy stellar mass, ∼30 per cent and ∼20 per cent of its star formation rate. Considering the compact blobs, we statistically estimated that massive clumps ( M ⋆ ≳ 10 9 M⊙ ) have lifetimes of ∼650 Myr, and the less massive ones (10 8 < M ⋆ < 10 9 M⊙ ) of ∼145 Myr. This supports simulations predicting long-lived clumps (lifetime ≳ 100 Myr). Finally, ≲30 per cent (13 per cent) of our sample galaxies are undergoing single (multiple) merger(s), they have a projected separation ≲10 kpc, and the typical mass ratio of our satellites is 1:5 (but ranges between 1:10 and 1:1), in agreement with literature results for close pair galaxies.